Organizational cultures that support community: Does the competing values framework help us understand experiences of community at work?. Issue 4 (18th October 2022) - Boyd, Neil M.; Larson, Sharon
Abstract: Recent evidence has shown that when employees experience perceptions of community at work (i.e., a sense of community and a sense of community responsibility), psychological well‐being and behavioral engagement improve (e.g., greater job engagement, organizational citizenship, and leadership). Recent evidence also shows that experiences of community, as a motivational state, are better able to predict employee outcomes compared to a series of factors that have long been studied in the general management (i.e., affective organizational commitment, organizational identity) and in the public management literature (i.e., public service motivation). However, we know less about the conditions that lead to perceptions of community experiences at work. One recent qualitative investigation exposed a series of organizational conditions that appear to stimulate perceptions of community at work including C‐Suite leadership support, organizational structure and context, characteristics of connection, managerial, job, and work unit characteristics, and responsibilities of human resource management professionals. The present study extends this study by empirically investigating organizational cultural conditions that are associated with perceptions of community at work. We test the ability of the Competing Values Framework, which includes constructs of Hierarchy, Market, Adhocracy, and Clan organizational cultures, and their ability to predict perceptions of the community. Findings showed that clan culture was most associated with perceptions of community in general and that clan culture within a department plays an important role in perceiving community at work. This study helps scholars understand cultural conditions that can lead to psychological experiences of community, it begins to frame cultural factors that scholars can empirically test in future studies, and it assists executives and managers in conceiving approaches to building cultures of community at work.